(untitled) (GEOmedia, 2016)
Natural hazards demand a rapid surveying of the crisis situation by means of Geomatics platforms, sensors and techniques. Remote sensing can provide a valuable source of broad scale information at each stage of the disaster management cycle, supporting scientists and authorities in the decision-making process. Geomatics-based procedures and techniques can be especially exploited in the emergency mapping domain and this research work provides a review of the current state-of-the-art of remote sensing techniques (platforms, sensors and commercial solutions) for rapid mapping applications. The management of time is defined as a priority and several solutions are discussed in order to pursue efficiency in both data acquisition and processing.